Nucleus accumbens projections: Validity and reliability of fiber reconstructions based on high‐resolution diffusion‐weighted MRI. Issue 18 (16th September 2021) - Rusche, Thilo; Kaufmann, Jörn; Voges, Jürgen
Abstract: Clinical effects of deep brain stimulation are largely mediated by the activation of myelinated axons. Hence, increasing attention has been paid in the past on targeting white matter tracts in addition to gray matter. Aims of the present study were: (i) visualization of discrete afferences and efferences of the nucleus accumbens (NAc), supposed to be a major hub of neural networks relating to mental disorders, using probabilistic fiber tractography and a data driven approach, and (ii) validation of the applied methodology for standardized routine clinical applications. MR‐data from 11 healthy subjects and 7 measurement sessions each were acquired on a 3T MRI‐scanner. For probabilistic fiber tracking the NAc as a seed region and the medial prefrontal cortex (mPFC), anterior cingulate cortex (ACC), amygdala (AMY), hippocampus (HPC), dorsomedial thalamus (dmT) and ventral tegmental area (VTA) as target regions were segmented for each subject and both hemispheres. To quantitatively assess the reliability and stability of the reconstructions, we filtered and clustered the individual fiber‐tracts (NAc to target) for each session and subject and performed a point‐by‐point calculation of the maximum cluster distances for intra‐subject comparison. The connectivity patterns formed by the obtained fibers were in good concordance with published data from tracer and/or fiber‐dissection studies. Furthermore, the reliability assessment of the (NAc to target)‐fiber‐tracts yielded to high correlations between the obtained clustered‐tracts. Using DBS with directional lead technology, the workflow elaborated in this study may guide selective electrical stimulation of NAc projections. Abstract : The nucleus accumbens (NAc), as a mesolimbic and dopaminergic relay station, and its efferent and afferent fiber‐projections play a central role within neuronal networks whose functions are impaired in various underlying neuro‐psychiatric disorders and could therefore be effective targets for the treatment of these disorders using deep brain stimulation (DBS). Therefore, the aim of the underlying work was a literature‐driven and diffusion‐weighted MRI‐based connectivity analysis, in vivo imaging, and subsequent inter‐ and intraproband comparison with respect to stability and reliability of the major neuronal fiber connections of the NAc. Overall, high anatomical validity, reliability, and stability were demonstrated for all considered and reconstructed NAc fiber connections, so that prospectively, from a clinical point of view, a valid preoperative fiber pathway reconstruction and thus a standardized preoperative intervention planning in the context of DBS would be possible and thus could improve the effectiveness and clinical outcome of this surgical method.